Progresivisme Pendidikan Agama Kristen di Tengah Kehidupan Masyarakat Majemuk - Sinauru, Retnalisa (STT Bala Keselamatan Palu, 2024)
Abstract: The article this discuss about the Progresivism of Christian Religion Education amid complex society existence. The Christian Religion Education progressively able to shape and transform individual attitude to be better di the midst of complex society existence. The diversity which is present in the midst of the complex society existence bring The Christian Religion Education actively bring the transformation for the education field. The Christian Religion Education in the complex society existence progressively being inclusive to every improvement especially to the advance oriented education. This research is is using book study qualitative research which have purpose to explain Christian Religion Education Progresivism in the midst of The Complex Society Existence that can give advancement to the education nowadays. With the result that, from the outcome of the study and so will gained the definition of progressivism, the definition of Christian Religion Education, the definition of complex society, the purpose of Christian Religioen education, The role of Christian religion education, in the progressivism, and the perspective of Christian Religion Education to progresivism amid the complex society. The Christian religion education contribute to the advancement to a education because the Christian Religion Education queit openly with every change as long it is not break the Christian Values. Abstrak: Artikel ini menjelaskan tentang Progresivisme Pendiidikan Agama Kriisten di Tengah Kehidupan Masyarrakat Maajemuk. Pendidikan Agama Kristen secara progresif mampu membentuk dan mengubah sikap individu untuk menjadi lebih baik di tengah kehidupan masyarakat majemuk. Keberagaman yang ada di tengah kehidupan masyarakat majemuk membawa Pendidikan Agama Kristen berperan aktif untuk memberikan perubahan bagi Pendidikan. Pendidikan Agama Kristen di tengah kehidupan masyarakat majemuk secara progresif terbuka terhadap segala perkembangan yang khususnya pada pendidikan yang berorientasi pada kemajuan. Peneliitian ini memakai penelitian kualitatif, studii pustaka yang bertujuan menjelaskan Progresivisme Pendidikan Agama Kristen di Tengah Kehiidupan Masyarrakat Majemuk yang dapat memberikan kemajuan bagi Pendidikan masa kini. Sehingga, dari hasil pembahasan maka akan diperoleh pengertian Progresivisme, pengertian Pendidikan Agama Kristen, pengertian Masyarakat Majemuk, Tujuan Pendidikan Agama Kristen, Peran Pendidikan Agama Kristen dalam Progresivisme, dan Perspektif Pendidikan Agama Kristen terhadap progresivisme di tengah Masyarakat Majemuk. Pendidikan Agama Kristen berkerjasama pada keemajuan suatuu pendidikan karena Pendidiikan Agama Kristen sangatt terrbuka dengan segalla perubahan sejauuh itu tidak melanggar nilai-nilai keKristenan.